PENGARUH DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP KINERJA KEUANGAN PADA PT WIJAYA KARYA (PERSERO) Tbk PERIODE 2014 - 2023 - Nur Huda, Abdullah; Sari Budhiarjo, Intan (Journal of Research and Publication Innovation, 2024)
This research aims to analyze the influence of Debt To Equity Ratio (DER) and Current Ratio (CR) on Financial Performance (ROE) at PT Wijaya Karya (Persero) Tbk in 2014 - 2023. The Independent Variable used in this research is Debt To Equity Ratio (DER) and Current Ratio (CR) while the dependent variable in this research is Financial Performance (ROE).The method used in this research is quantitative analysis with the data source obtained from the company's annual report published on the company's website for the period 2014 to 2023. The partial research results show that the Debt to Equity Ratio has a positive and significant effect on (ROE), with the result that Tcount value 3.414 > Ttable 2.30600 with a significant value of 0.011 < 0.05. Thus it can be concluded that Ho is rejected and Ha is accepted. Which means that there is a positive and significant influence between the Debt to Equity Ratio on the financial performance (ROE) of PT Wijaya Karya (Persero) Tbk. The partial research results of the Current Ratio have no and significant effect on (ROE), with the result that the Tcount value is 1.356 < Ttable 2.30600 with a significant value of 0.217 > 0.05. Thus it can be concluded that Ho is accepted and Ha is rejected. Which means there is no influence between the Current Ratio on the financial performance of PT Wijaya Karya (Persero) Tbk. The results of research simultaneously Debt to Equity Ratio, Current Ratio show that there is an influence and it is significant, by obtaining an Fcount value of 8.826 > Ftable 4.74 at a significance level of F 0.012 < 0.05. So it can be concluded that the Debt to Equity Ratio and Current Ratio together (simultaneously) influence Return On Equity (ROE), PT Wijaya Karya (Persero) Tbk.